Laser‐Directed Foaming of Hydroplastic Polyelectrolyte Films toward Tunable Structures and Programmable Routes. (7th November 2021) - Zhang, Da; Li, Qing‐Shuang; Liang, Zi‐Xuan; Chen, Xia‐Chao; Hao, Junran; Yao, Juming; Lu, Chun‐Xin; Zhou, Yahong; Jiang, Lei
Abstract: Although many methods have been developed to create porous structures within polyelectrolyte films, it remains a challenge to conveniently define the spatial distribution of these structures. Herein, a simple, universal strategy with a high flexibility in programming porous regions throughout polyelectrolyte films is reported. This strategy is performed with the aid of laser scanning and the emergence of porous regions precisely tails after the moving path of laser beams. Quite different from previous strategies, the pore‐forming mechanism relies on laser‐triggered generation of gas to foam the films, which can be regulated by the content of photo‐sensitive groups, the intensity of laser beams, and the supramolecular interactions between polyelectrolyte chains. A prerequisite to succeed the foaming of polyelectrolyte films is to irradiate them under water, where the mobility of polyelectrolytes is activated to accommodate the pore formation within the films. Although many pore‐forming mechanisms involve aqueous systems, the porous structures here can be well preserved during drying procedures, which is hardly realized for conventional methods due to the formation of capillary pressure. The resulting polyelectrolyte films with patterned porosity can be quite useful in many fields, including but not limited to information display, surface wettability, and cell behavior manipulation. Abstract : A simple, universal strategy is proposed to achieve high flexibility in programming porous regions throughout polyelectrolyte films. The pore‐forming method here relies on photo‐triggered generation of gas to foam the films and is performed with the aid of laser scanning to make the emergence of porous regions precisely follow the moving path of laser beams.